Proaktives Management von Anforderungsänderungen in der Entwicklung komplexer technischer Systeme - Oleff, Christian
Anforderungsänderungen sind ein wesentlicher Grund für Ineffizienzen und Projektfehlschläge in der Entwicklung komplexer technischer Systeme. Proaktives Management von Anforderungsänderungen hat das Potenzial, den Umgang mit Anforderungsänderungen effizienter zu gestalten. Dafür ist ein systematischer Ansatz erforderlich, der eine ganzheitliche Bewertung und Handhabung des Änderungsrisikos im industriellen Entwicklungskontext ermöglicht. Im Rahmen dieser Dissertation wird mit der ProMaRC-Methodik ein neuartiger Ansatz für das proaktive Management von Anforderungsänderungen vorgestellt. Die Methodik wurde in enger Zusammenarbeit mit Industrieanwender:innen aus der Automobilindustrie entwickelt und anhand von fünf Fallstudien validiert. Mittels automatisierter Abhängigkeitsanalyse auf Grundlage künstlicher Intelligenz wird der Anwendungsaufwand gegenüber bestehenden Ansätzen reduziert. Die teilautomatisierte Bewertung und Handhabung der Änderungswahrscheinlichkeit und -auswirkung erfolgt anhand eines modifizierten PageRank-Algorithmus und umfasst erstmalig alle für die Risikoanalyse relevanten Einflussfaktoren. Die Validierung belegt, dass durch die ProMaRC-Methodik eine überzeugende Kombination aus praxistauglichem Anwendungsaufwand und Vollständigkeit der Analyse erzielt wird. Damit erschließt diese Dissertation das bisher kaum beachtete Forschungsfeld des proaktiven Managements von Anforderungsänderungen und fördert eine effizientere Produktentwicklung.

Systems Engineering - verstehen und industriell umsetzen - Gräßler, Iris; Oleff, Christian
Wie werden technische Systeme zeitgemäß entwickelt, die in Komplexität und Anspruch alles bisher Dagewesene übertreffen? Darauf gibt Systems Engineering Antworten. Bisherige Beschreibungen sind für den Maschinenbau aber oft schwer greifbar und zu unkonkret. Dieses Buch bricht den internationalen Stand der Wissenschaft auf das Wesentliche herunter und beschreibt praxisnah die Kernelemente des Systems Engineering. Eine konkrete Schritt-für-Schritt Anleitung ebnet den Weg für den erfolgreichen Transfer aus der klassischen Produktentwicklung hin zum Systems Engineering. Die Inhalte werden grafisch professionell und bewusst lebendig vermittelt. So wird nicht nur ein fundiertes Systems Engineering-Verständnis geschaffen, sondern auch die Basis für Kommunikation und Umsetzung im Unternehmen gelegt.

Automated Requirement Dependency Analysis for Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Hieb, Michael; Preuß, Daniel (Proceedings of the Design Society)
Abstract Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by means of a case example, 4 development projects and 3 workshops with industry experts.

Extended RFLP for complex technical systems - Gräßler, Iris; Wiechel, Dominik; Oleff, Christian

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Model-Based Effect-Chain Analysis for Complex Systems - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Preuß, Daniel; Oleff, Christian (Proceedings of the Design Society)
Abstract Effect chain modeling approaches are applied to model cause-effect relations and analyze affected elements and dependencies. In this paper a systematic literature research is conducted to derive main characteristics and limitations of existing approaches. Then, the Model-based Effect Chain Analysis (MECA) method is introduced. Evaluation proves applicability of the method by means of a case example. This is done in the context of a project with a German automotive company. In the project 66 workshops were conducted to model certification-compliant effect chains in accordance to the UN ECE 156.

Modeling and analysis of functional variance of complex technical systems - Menninger, Bastian; Wiechel, Dominik; Rackow, Sascha; Höpfner, Gregor; Oleff, Christian; Berroth, Joerg; Gräßler, Iris; Jacobs, Georg (DS 119: Proceedings of the 33rd Symposium Design for X (DFX2022))

Strategisch-technische Anforderungsanalyse - Gräßler, Iris; Oleff, Christian; Scholle, Philipp (Mehrzieloptimierte und durchgängig automatisierte Bauteilentwicklung für Additive Fertigungsverfahren im Produktentstehungsprozess)

Holistic change propagation and impact analysis in requirements management - Gräßler, Iris; Oleff, Christian; Preuß, Daniel
In developing complex technical systems, requirements are subject to continuous change. Systematic and holistic change impact analysis and proactive measures are required for reducing the number of requirement changes and their negative impact. There is no method to analyse the holistic impact of a requirement change in the context of developing complex technical systems. Holistic analysis requires to consider the local effects of requirement changes as well as effects from change propagation. To develop an approach for holistic change propagation and impact analysis, twelve performance goals are defined. Those are derived from a state of research analysis as well as an industry workshop. A three-step method is proposed. Firstly, requirement dependencies that cause change propagation are detected. Secondly, critical requirements are automatically identified based on a Page Rank algorithm. Thirdly, change impact of critical requirements is analysed based on a guideline. Validation proves that ten goals are fulfilled and two are partly fulfilled. The method addresses major shortcomings of preceding research and enables sound decision making for development engineers both before a change occurs and during decision process on a change request. This helps to reduce negative change impact in development projects and the risk of project failure.

Handling of explicit Uncertainty in Requirements Change Management - Gräßler, Iris; Pottebaum, Jens; Oleff, Christian; Preuß, Daniel (Proceedings of the Design Society)
Abstract Innovation projects are characterized by numerous uncertainties. Typical concepts in development management like the application of safety coefficients imply limitations of the solution space. In contrast, explicit handling of uncertainties can support engineers in understanding the problem space and in utilising the full potential of the design space along iterative product development steps. As a result from literature analysis, there is a lack of a support for product development that addresses the specific problem of uncertainty and risk in the context of requirement changes. The aim of the contribution at hand is to enhance the efficient development of complex interdisciplinary systems by enabling uncertainty handling in requirements change management. Based on a classification of uncertainty types resulting in a descriptive model, risk management measures are identified to support requirements engineers. The proposed method includes identification & modelling, analysis, treatment and monitoring of risks and counter-measures. By applying this method, engineers are supported in adopting agile approaches and enabling flexible Requirements Engineering.

Automatisierte Identifikation und Charakterisierung von Anforderungsabhängigkeiten – Literaturstudie zum Vergleich von Lösungsansätzen - Gräßler, Iris; Preuß, Daniel; Oleff, Christian (Proceedings of the 31st Symposium Design for X (DFX2020); 16. - 18. Sep. 2020)

Method for Systematic Assessment of Requirement Change Risk in Industrial Practice - Gräßler, Iris; Oleff, Christian; Scholle, Philipp (Applied Sciences 23/2020 (23))

A METHODICAL APPROACH TO INTEGRATED PRODUCT DEVELOPMENT IN TOTAL HIP ARTHROPLASTY - Ley, P.-P.; Wirths, L.; Oleff, Christian; Jungreitmayr, F.; Vajna, S.; Paetzold, K.; Borg, J. C. (Proceedings of the Design Society: DESIGN Conference)
Abstract Hip joint arthroplasty is considered to be a safe, successful and cost-effective procedure to restore hip joint functionality. However, a successful hip joint arthroplasty affects different stakeholders e.g. patient and surgeon and depends on various influencing factors within the product life cycle as well as the applied technological opportunities. Due to the complex dependencies between influencing factors, technological opportunities and stakeholders, this contribution introduces an IPD-based approach to improve the quality of total hip arthroplasties.

Risikoorientierte Analyse und Handhabung von Anforderungsänderungen - Gräßler, Iris; Oleff, Christian (Design fox X - Beiträge zum 30. DfX-Symposium September 2019, Band 30)

Priorisierung von Anforderungen für die Entwicklung mechatronischer Systeme - Gräßler, Iris; Oleff, Christian; Scholle, Philipp (Fachtagung Mechatronik 2019 Paderborn)
In diesem Beitrag wird ein Ansatz vorgestellt, welcher die Bewertung des Risikos von Anforderungsänderungen in der Entwicklung mechatronischer Systeme ermöglicht. Ausgehend von einer Anforderungsliste werden die Wechselwirkungen in einer Requirements Structure Matrix (RSM) teilautomatisch erfasst. Parallel werden Anforderungen in Bezug auf ihren Ursprung („Einflussbereich“) kategorisiert und darauf aufbauend priorisiert. Diese Priorisierung basiert auf dem Veränderungsrisiko und wird durch die drei Kriterien „Dynamik“, „Unsicherheit der Wissensbasis“ und „Relevanz für den Entwicklungsprozess“ charakterisiert. Das Vorgehen wird anhand strukturierter Interviews mit Projektleitern und Entwicklern und der Fallstudie eines Pedelecs als mechatronischem System validiert. Durch die Anwendung der Methode können disziplinübergreifende Abhängigkeiten von Anforderungen zur Reduktion von Iterationen in der Entwicklung mechatronischer Systeme – wie dem Pedelec – berücksichtigt werden.

Augmented Reality für die Vermittlung von Systems Engineering - Gräßler, Iris; Oleff, Christian; Taplick, Patrick (Fachtagung Mechatronik 2019 Paderborn)
Systems Engineering befähigt Entwicklungsteams, die Komplexität mechatronischer Systeme insbesondere in Bezug auf die Vernetzung von Systemelementen handhabbar zu machen. Die Methodik beruht auf dem Ansatz des System-denkens, das ein tiefgreifendes Verständnis mechatronischer Systeme erfordert. Traditionelle Lehrkonzepte stoßen bei der Vermittlung von SE-Kompetenzen und speziell dem Systemdenken an ihre Grenzen [1]. Sprachen wie die Systems Modeling Language (SysML) erlauben die Beschreibung von Systemen und die entwicklungsphasenübergreifende Ver-bindung von Daten und Informationen. Sie unterstützen sowohl das individuelle als auch das kollektive Systemdenken [2]. Mittels Augmented Reality können mechatronische Systeme mit Informationen aus virtuellen Modellen angereichert und damit das Verständnis für komplexe Sachverhalte unterstützt werden (z.B. [3]). Die durch einen Demonstrator unterstützte Analyse zeigt, dass durch die situative, bedarfsgerechte und lernzielorientierte Visualisierung von Informa-tionen der Aufbau von Systems Engineering Kompetenzen gefördert werden können.

Method for Analysing Requirement Change Propagation based on a Modified Pagerank Algorithm - Gräßler, Iris; Thiele, Henrik; Oleff, Christian; Scholle, Philipp; Schulze, Veronika (Proceedings of the Design Society: International Conference on Engineering Design)
Complexity of products and systems is increasing through digitalization, interdisciplinarity as well as high technology maturity and new business models. In consequence, new product development (NPD) projects need to manage and satisfy a large number of requirements from a broad range of stakeholders. Yet, NPD projects are often delayed due to requirement changes. In this paper, a new method for analyzing requirement change propagation is presented. The method is based on the assessment of requirement interrelations structured in a requirements structure matrix by a modified page-rank algorithm. By the method, a high number of strongly interrelated requirements can be analyzed in an efficient manner. Additionally, higher-level interrelations as well as the relative weights of requirements are also incorporated in the analysis. Hereby, an efficient holistic approach towards the analysis of requirement change propagation is proposed.

Role Model for Systems Engineering Application - Gräßler, Iris; Oleff, Christian; Hentze, Julian (Proceedings of the Design Society: International Conference on Engineering Design)

Methode zur Bewertung von Anforderungsänderungen additiv gefertigter Produkte - Gräßler, Iris; Oleff, Christian; Scholle, Philipp (Design for X - Beiträge zum 29. DfX-Symposium, Band 29)

Systems Engineering Competencies in Academic Education - Gräßler, Iris; Hentze, Julian; Oleff, Christian (13th System of Systems Engineering Conference (SoSE))

Semi-Automatized Assessment of Requirement Interrelations - Gräßler, Iris; Scholle, Philipp; Hentze, Julian; Oleff, Christian (Proceedings of the DESIGN 2018 15th International Design Conference)
Changing requirements have a broad impact on product development processes. In this paper, a novel approach towards structuring requirements is proposed. Based on a requirements list, interrelations of requirements are assessed semi-automatically by a rule basis. Here, generic interrelations funded on either physical fundamentals or working principles are recorded. By this approach, requirements structure matrices are derived semi-automatically. Combined with selecting critical requirements based on structured criterions, iterations due to changing requirements will be reduced.